2019
DOI: 10.1016/j.mambio.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel real-time PCR species identification assays for British and Irish bats and their application to a non-invasive survey of bat roosts in Ireland

Abstract: Novel real-time PCR species identification assays for British and Irish bats and their application to a non-invasive survey of bat roosts in Ireland,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…1) under license from NPWS (licence number DER/BAT 2016-29). Each DNA extract was identified to species and sex using real-time PCR assays (Harrington 2018;Harrington et al 2019) and identified to individual level using a panel of seven microsatellite markers originally designed by Puechmaille et al (2005) and re-designed and optimised by Harrington (2018). Twenty-four R. hipposideros samples were used as part of this DNA metabarcoding work and evenly represented sex (n = 12 for male and female samples) and location (n = 4 samples from each of the six roosts with sex evenly represented at each roost).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) under license from NPWS (licence number DER/BAT 2016-29). Each DNA extract was identified to species and sex using real-time PCR assays (Harrington 2018;Harrington et al 2019) and identified to individual level using a panel of seven microsatellite markers originally designed by Puechmaille et al (2005) and re-designed and optimised by Harrington (2018). Twenty-four R. hipposideros samples were used as part of this DNA metabarcoding work and evenly represented sex (n = 12 for male and female samples) and location (n = 4 samples from each of the six roosts with sex evenly represented at each roost).…”
Section: Methodsmentioning
confidence: 99%
“…Indirect monitoring of biodiversity via environmental sources or the diet of a predator, such as insectivorous bat species, can provide data regarding the composition and interactions of species within a community (de Sousa et al 2019), providing a more holistic approach to assessment. Bats are described as indicators of diversity and can be studied relatively easily across landscapes using well-established surveillance methods (Jones et al 2009;Park 2015;Russo and Jones 2015;Russo et al 2018;Harrington et al 2019). Bats are considered specialised hunters, with different species seeking areas of open, narrow and edge space habitats to hunt (Denzinger and Schnitzler 2013;Heim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large sheets of plastic were laid on the ground within each roost and left for a period of one to two weeks. Droppings were collected and stored frozen at -20°C or DNA extracted within 24 hours using the Zymo Research Genomic DNA TM -Tissue MicroPrep kit following the protocol used for faecal DNA extraction in Harrington et al (2019). Each DNA extract was identified to species level using a species-specific real-time PCR assay (Harrington et al 2019) and identified to individual level using a panel of seven microsatellite markers originally designed by Puechmaille et al (2005) and redesigned and optimised to work efficiently with faecal DNA by Harrington (2018) via two multiplex PCRs.…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%